2001
DOI: 10.1002/1529-0131(200111)44:11<2620::aid-art442>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin V? light chain gene usage in patients with Sj�gren's syndrome

Abstract: Objective To determine whether patients with Sjögren's syndrome (SS) have abnormalities in Ig Vλ and Jλ gene usage, differences in somatic hypermutation, defects in selection, or indications for perturbations of B cell maturation. Methods Individual peripheral B cells from SS patients were analyzed for their Vλ gene usage by single‐cell polymerase chain reaction amplification of genomic DNA and compared with those from normal controls. Results Molecular differences from controls in Vλ–Jλ recombination were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 57 publications
1
34
0
3
Order By: Relevance
“…The existence of mutated, in-frame, nonexpressed IGKV-J rearrangements might be considered as indirect evidence for secondary rearrangements after the onset of somatic hypermutation (SHM). Chronic antigen stimulation may trigger secondary rearrangements at the IGH or the IGK/IGL loci (53,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Although the occurrence of secondary rearrangements in normal peripheral B cells was considered as doubtful or-at best-limited (67), several studies indicate that secondary rearrangements may occur following SHM, particularly in a setting of autoimmunity or neoplasia (58,60,62,66,68).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of mutated, in-frame, nonexpressed IGKV-J rearrangements might be considered as indirect evidence for secondary rearrangements after the onset of somatic hypermutation (SHM). Chronic antigen stimulation may trigger secondary rearrangements at the IGH or the IGK/IGL loci (53,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Although the occurrence of secondary rearrangements in normal peripheral B cells was considered as doubtful or-at best-limited (67), several studies indicate that secondary rearrangements may occur following SHM, particularly in a setting of autoimmunity or neoplasia (58,60,62,66,68).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to RA patients, patients with SS appear to have decreased receptor editing/revision as identified by enhanced usage of V proximal-located J L segments, likely reflecting a defect in or infrequent usage of receptor editing (40,41). In this regard, a recent analysis of 6 monoclonal antibodies with RF activity obtained from the peripheral blood of SS patients showed that all used V -proximal J 2/3 gene segments (74), consistent with the conclusion that receptor editing/revision may be defective in SS.…”
Section: Receptor Editing and Autoimmunitymentioning
confidence: 94%
“…The majority of available data do not support this hypothesis but rather suggest an absence of genetic abnormalities, causing B cells to generate an autoreactive repertoire in patients with systemic autoimmune diseases (38)(39)(40)(41)(42)76,77). Thus, no genetic polymorphisms of the heavy and light chain Ig V gene loci and no fundamental abnormalities in the V(D)J recombination process underlie the generation of autoantibodies.…”
Section: Selective Influences Shaping the Ig V Gene Repertoirementioning
confidence: 99%
See 2 more Smart Citations